Motivation for Academic Achievement Among Students at State Senior High School 4 Pekanbaru - Nurul Haqqi Ramadhani; Hesti Asriwandari (SOCIAL PEDAGOGY: Journal of Social Science Education, 2026)
Education serves as a platform for developing students’ potential; however, new educational institutions often face significant challenges in fostering a spirit of competition. This study aims to determine the level of students’ achievement motivation and to identify the factors influencing it at Madrasah Aliyah Negeri 4 Pekanbaru. Using a descriptive quantitative method, data were collected via a questionnaire from 78 respondents and analysed using descriptive statistics, specifically measures of central tendency (mean) and frequency distribution calculations, with the aid of SPSS Version 25. The results of the study indicate that students’ achievement motivation falls into the high category (92.3%), driven by a strong need to achieve. The factors influencing both internal and external aspects also fall into the high category, at 85.9% and 92.3% respectively. Internal factors such as interest, talent, and intelligence, as well as external factors in the form of support from the family and madrasah environments, were found to be interrelated in influencing students’ achievement motivation. This study concludes that a combination of internal and external factors is key to fostering students’ achievement motivation at Madrasah Aliyah Negeri 4 Pekanbaru.